2011
DOI: 10.1080/09654313.2011.586175
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Location of R&D and Production Activities: Trends in the Automotive Industry

Abstract: This article analyses the location strategies pursued by multinational corporations. The empirical study is based on automobile MNCs of Triad nations, which need to optimize the location of their activities in order to remain competitive. The main objective of the paper is to determine to which extent automotive MNCs are globalized or regionalized. The analysis focuses on production and R&D activities, which play a strategic role in the global value chain of companies. The arguments presented show that, whilst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 31 publications
(44 reference statements)
0
21
0
5
Order By: Relevance
“…Leurs investigations révèlent que le PIB et la population d'un pays continuent d'exercer une influence déterminante sur les choix de localisation, même si le premier facteur est devenu moins important que le second. L'exemple de l'industrie automobile montre que si, dans le passé, la plupart des constructeurs des pays de la Triade concentraient leurs activités de production et de R&D dans leur pays ou région d'origine, ils diversifient aujourd'hui les localisations de leurs investissements (Colovic et Mayrhofer, 2011), notamment pour les usines de production.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Leurs investigations révèlent que le PIB et la population d'un pays continuent d'exercer une influence déterminante sur les choix de localisation, même si le premier facteur est devenu moins important que le second. L'exemple de l'industrie automobile montre que si, dans le passé, la plupart des constructeurs des pays de la Triade concentraient leurs activités de production et de R&D dans leur pays ou région d'origine, ils diversifient aujourd'hui les localisations de leurs investissements (Colovic et Mayrhofer, 2011), notamment pour les usines de production.…”
Section: Resultsunclassified
“…Sous l'impulsion de la globalisation des marchés, elles ont choisi de diversifier l'implantation géographique de leurs filiales. Les chiffres fournis par la CNUCED (2011) (Colovic et Mayrhofer, 2011;UNCTAD, 2011). Un grand nombre de FMN dispose désormais d'un « portefeuille » de filiales localisées à travers le monde qui sont amenées à contribuer à leur chaîne de valeur globale.…”
Section: Introductionunclassified
“…Siedschlag et al (2009), for instance, considered 446 location de-cisions of foreign affiliates in the R&D sector incorporated in the European Union over 1999-2006. Through the analysis they suggested that, on average, the location probability increases with the market demand, low production cost, R&D intensity, flexibility of labor markets, access to skilled labor, and information technology infrastructure. In the same direction, Colovic and Mayrhofer (2011) found that in the automotive industry R&D centers are located close to the production activities in order to permit flexibility and low production cost. Serapio and Dalton (1999) analyzed 701 R&D foreign centers in the United States, finding that 75.2% of those structures were lo-cated in the 11 principal States of the country.…”
Section: Rational Model Studiesmentioning
confidence: 96%
“…L'étude du secteur automobile par exemple, montre que les constructeurs issus des pays de la Triade diversifient aujourd'hui la localisation de leurs activités de production en faveur des pays émergents alors que, dans le passé, ils avaient l'habitude de concentrer leurs activités de production dans leur pays ou région d'origine (Colovic et Mayrhofer, 2011). De même en est-il pour la production de véhicules industriels qui, selon le rapport de l'organisation internationale des constructeurs d'automobiles (OICA, 2013 1 ), augmente dans les pays tels que le Brésil (+43,1 %), l'Argentine (+28,3 %), l'Afrique du Sud (+12,2 %) et la Chine (+10,4 %), alors qu'elle diminue en Europe (-14 %) et aux USA (-6 %).…”
Section: Les Chaines De Valeurs Mondialesunclassified